Designing and Implementing Unemployment Benefit Systems in Middle and Low Income Countries : Key Choices between Insurance and Savings Accounts - Robalino, David A.; Weber, Michael (World Bank, Washington, DC, 2014)
Several middle income countries are considering reforms of severance pay regulations to both increase flexibility for firms and better protect workers. Policy discussions then often revolve around whether to adopt an unemployment insurance (UI) scheme or unemployment individual savings accounts (UISAs). Proponents of the first emphasize its ability to pool risks and introduce an element of solidarity. Critics point to its potentially negative effects on labor supply as individuals can have fewer incentives to seek, take or keep jobs. In this paper, the authors show that UI and UISAs are, in fact, particular cases of a more general design and that the crucial policy choice is in terms of how redistribution - to cover benefits for those who cannot save enough is financed. The authors outline key features of this general design and discuss trade-offs and possible solutions. The authors discusses issues related to implementation and show how recent technological developments around biometric identification can facilitate the monitoring of conditionalities related to participation in job-search and training activities.